Penerapan Teknik Memindai dalam Meningkatkan Kemampuan Membaca Kritis Siswa Sekolah Dasar Cikurubug - Cecep Karyana (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
Critical reading is one of four types of reading comprehension skills. Critical reading is the activity of reading silently carried out for the purpose of learning so as to gain broader insights about something that has been read. Based on observations, it shows that the critical reading ability of fifth grade students at SDN Cikurubuk is still lacking. The cause of the problem of critical reading skills class V is still lacking, Teacher has not used appropriate reading learning techniques. This study aims to describe the application of scanning techniques (scanning) on the material to find information quickly from various special texts to improve students' critical reading skills. This study uses a class action research design, which was carried out in 2 cycles. The subjects of this study were fifth grade students at SDN Cikurubuk. Data collection techniques and research instruments used were tests. The data analysis technique uses descriptive qualitative and quantitative. The results showed that the critical reading ability of students in the first cycle obtained a percentage of completeness of 55.17 %% and 89.66% in the second cycle. The obstacles that arise in the ability to read critically by applying scanning techniques can be overcome by creating a discussion group of up to 3 students and providing guidance on how to find specific information, important details and make conclusions from specific information with the right steps. So, it can be concluded by applying the scanning technique to improve the critical reading skills of fifth grade students at SDN Cikurubuk.